A RANDOMIZED, GROUP-PARALLEL COMPARATIVE TRIAL OF THE SUPPRESSIVE EFFECT OF CHINESE TRADITIONAL MEDICINE, SHEN-MI-TANG (SHIN-PI-TO), COMPARED TO SODIUM ORAMOYLYCATE INHALATION IN IMPROVING SUBJECTIVE AND OBJECTIVE SYMPTOMS IN BRONCHIAL ASTHMATICS - Goto, Gracy Hiroe; Nishizawa, Yasuko; Fushiki, Shinji; Yoshioka, Fumi; Nishizawa, Yoshio (JIBI INKOKA TEMBO, 2004)
Shen-mi-tang (Shin-pi-to, SBT) is a well-known suppressor of 5-lypoxygenase as reported by Hamazaki's et al. SBT also has many other antiallergic and antiinflammatory effects. If we can use SBT tropically on bronchoallergic portions, we see the same phenomena occurring in in vivo and in vitro experiments.To obtain a high SBT concentration on the bronchoalligopathological portion, we sutudied kampo herb medicine, i.e., SBT inhalation therapy. After informed consent was obtained, 161 patients were divided into two groups (Group A, n = 81) (Group B, n = 80). Under the same conditions for different drugs, patients in group A inhaled SBT (500 μg/1 capsule, 4 times/day) for 3 years. Patients in group B inhaled sodium cromoglicate (CSCG) (20 mg/1 capsule) in the same administraton using DSCG-spinhela. The difference between DSCG and SBT in capsules was not recognized because these capsules were identical capsule using for DSCG, i.e., baseline clinical characteristics did not significantly differ between groups. At the end point, subjective symptoms such as asthmatic score, PEF titer, and resqure time of β 2 agonist use decreased significantly. Therapeutic drugs also decreased significantly in group A (p < 0.001). In group B, these parameters increased significantly. (p< 0.05). (p< 0.001 vs Group B) Adverse side effects and the appearance of abnormal laboratory data during this trial was lower in group A. In global improvement, group A showed 61.9%, but group B only 5.6% (p< 0.001). These reasons are discussed in this paper.